Ferrocenylethynyl derivatives of nucleoside triphosphates: synthesis, incorporation, electrochemistry, and bioanalytical applications - Brázdilová, Petra; Vrábel, Milan; Pohl, Radek; Pivonková, Hana; Havran, Ludek; Hocek, Michal; Fojta, Miroslav (Chemistry (Weinheim an der Bergstrasse, Germany), 2007)
Modified dATP (2'-deoxyadenosine-5'-triphosphate) and dUTP (2'-deoxyuridine-5'-triphosphate) bearing ferrocene (Fc) labels linked via a conjugate acetylene spacer were prepared by single-step aqueous-phase cross-coupling reactions of 7-iodo-7-deaza-dATP or 5-iodo-dUTP with ethynylferrocene. The Fc-labeled dNTPs were good substrates for DNA polymerases and were efficiently incorporated to DNA by primer extension (PEX). Electrochemical analysis of the 2'-deoxyribonucleoside triphosphates (dNTPs) and PEX products revealed significant differences in redox potentials of the Fc label bound either to U or to 7-deazaA and between isolated dNTPs and conjugates incorporated to DNA. Prospective bioanalytical applications are outlined.
Keywords: fosfáty; Nucleotides; nukleotidy; Ferrous Compounds; molekulární struktura; Molecular Structure; elektrochemie; Phosphates; železnaté sloučeniny; Electrochemistry